The Analysis of Decision of The Constitutional Court Number 97/Puu-Xiv/2016 Concerning Population Administration on The Rights and Position of Believers - Abidin Latua (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
The research is to take a closer and explicit look at the position of believers in the Constitutional Court's decision through synchronizing the existence or existence of believers in Yogyakarta. In order to ensure whether or not these concerns are true, and to what extent are the rights and positions guaranteed in the decision of the Constitutional Court, and what is the position of believers in the Constitutional Court Decision Number 97/PUUXIV/2016 concerning Population administration in terms of perspective (Maqāṣid ash-Syarī‘ah). The type of legal research used in the preparation of this research is field research, which is conducting direct observations with in-depth interviews with sources that have been determined based on the researcher's knowledge using the purposive sampling method. The approach used in this research is normative juridical (Statute Approach) and empirical or sociological juridical. The normative juridical approach is carried out by referring to the legal norms contained in the legislation, decisions and legal norms that exist in society. The results of the research show that the considerations of the judges of the Constitutional Court related to the Philosophical, Textual, and Sociological Legal Interpreters in deciding the case Number 97/PUU-XIV/2016 concerning the review of the Population Administration Law, have fulfilled the basic rights of believers and provide justice to adherents of the sect. trust, then when viewed with the study of Human Rights the Constitutional Court's